Optimum Parameters for Machining Metal Matrix Composite - Boswell, Brian; Islam, Mohammad Nazrul; Pramanik, Alokesh (Springer, 2014)
The need for optimum machining parameters has always been of paramount importance for metal cutting. The economics of the process largely depends on selecting the best machining parameters. However, the additional challenge of being environmentally friendly in production while still being cost effective is now imperative. Machining conditions are not always conducive in reducing the carbon footprint when cutting material with a low machinability rating. This is particularly pertinent when aerospace material such as Boron Carbide Particle Reinforced Aluminium Alloy (AMC220bc) is machined. This material falls under the category of a particulate reinforced Metal Matrix Composite (MMC), where the ceramic fibers disrupt the flow of electrons. The result is a decrease in thermal conductivity causing the tool interface temperature to increase, reducing tool life. This research will determine the optimum economic and sustainable machining parameters for this material.